Direct solution of plasticity problems in soils by the method of characteristics. - Houlsby, G; Wroth, C (Balkema, 1983)
The application of similar methods to problems of axial symmetry, and to soils with non-homogeneous properties is described and some illustrative examples given. The method of characteristics may also be used for the solution of the plastic displacement equations, although the exact form which these equations should take is still a matter of controversy. -from Authors